The effectiveness of public service announcements / Nor Afiqah Izzati Hassan, Siti Nur Farrah Faadiah Ab Ghani and Aini Faezah Ramlan - Hassan, Nor Afiqah Izzati; Ab Ghani, Siti Nur Farrah Faadiah; Ramlan, Aini Faezah (Faculty of Communication & Media Studies, 2022)
Public Service Announcement (PSA) is the informative short films that made with the purpose to increase and give awareness to the society or creating behavioural changes. Media plays an important role in giving awareness to the public. Lots of Public service announcements (PSA) had been made in various platform as one of the used of PSA is to give awareness to the public. For example, through television, short video, radio, social media and others platform. Also, PSA had started to broadcasted on the internet as an alternative advertising media in order to reach out to the younger generation. As many as 10 journals were chosen wisely after going through some process corresponded to the criteria which is related to PSA. Through the findings, it shows whether PSAs effective to the public.